Assessment of quality of care provided at a tertiary hospital of Sikkim by patient's degree of responsiveness - Rahman, Hafizur; Khalda, Ezzat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Quality of care is concerned with the interface between provider and patients, between health services and community. The aim of the current study was to evaluate the quality of provided health care and patient experiences at a tertiary hospital based on the concept of responsiveness. Methods: This was a cross-sectional survey among reproductive women of Central Referral Hospital over a period of 5 months from August 2016 to December 2016. A pre-designed, pretested, self-administered response questionnaire on rate of service utilization using the WHO health system responsiveness modulewas used. Results: A total of 450 women were approached and requested to participate during the study period of which 374 women completed the survey. According to the evaluation of in-patient care (Table 2), "able to change doctor if wanted" showed the lowest degree of responsiveness (52.7%). A significant proportion of patients experienced discrimination for different reasons: 9.6% reported feeling they had been treated worse than others because of lack of money, while a similar proportion reported they had been discriminated for the language they speak or because they were having insurance from a company. Conclusions: Health care access in terms of prolong waiting time in the reception and before being attended by doctor, difficulty to change doctor when wanted and discriminatory experiences were identified as priority areas for actions to improve responsiveness and patient satisfaction.